Atomically thin noble metal dichalcogenide: a broadband mid-infrared semiconductor - Yu, Xuechao (2018)
The interest in mid-infrared technologies surrounds plenty of important optoelectronic applications ranging from optical communications, biomedical imaging to night vision cameras and so on. Although narrow bandgap semiconductors such as Mercury Cadmium Telluride and Indium Antimonide, and quantum superlattices based on inter-subband transitions in wide bandgap semiconductors have been employed for mid-infrared applications, it remains a daunting challenge to search for other materials that possess suitable bandgaps in this wavelength range. Here, we demonstrate experimentally for the first time that two-dimensional atomically-thin PtSe2 has a variable bandgap in the mid-infrared via layer and defect engineering. Here, we show that bilayer PtSe2 combined with defects modulation possesses strong light absorption in the mid-infrared regime and we realize a midinfrared photoconductive detector operating in a broadband mid-infrared range. Our results pave the way for atomically-thin 2D noble metal dichalcogenides to be employed in highperformancemid-infrared optoelectronic devices.